PENGELOLAAN KOLABORASI HUTAN PENDIDIKAN DAN PELATIHAN JAMPANG TENGAH – SUKABUMI - Jaenal, Enjen; AT, Mulyadi; Supriono, Bambang (Jurnal Nusa Sylva, 2012)
Collaborative forest management Training Central Jampang by involving the local community, is one alternative in the management of the Forest Training. Where the Forest Training functions as a means of supporting education and training conducted by the Forestry Training Centre can be run in accordance with the vision , mission and goals without ignoring the existence of the people residing in the vicinity. The purpose of the study is to determine the condition and potential of Forest Training Central Jampang to organize and conduct an evaluation of Training Forest neighborhood becomes a means of integrated practice models in the context of forestry and agricultural land rehabilitation, soil and water conservation as well as identify and implement forest management activities collaboratively Training Jampang Tengan between forest managers and local residents, especially farmers. Training Forest Middle Jampang condition is quite alarming because many suffered damage, such as physical buildings and plots and the current instance has been partially improved. Forest Development Training Central Jampang done through empowerment and community development activities around the Forest Training form of collaborative activities such as beekeeping, forest utilization patterns so as to provide benefit agroforestry economic, social, and technology to communities around the Forest Training.